Short communication: Influence of restorative material and cement on the stress distribution of posterior resin-bonded fixed dental prostheses: 3D finite element analysis - Tribst, João Paulo M. [UNESP]; Dal Piva, Amanda M.O. [UNESP]; de Melo, Renata M. [UNESP]; Borges, Alexandre L.S. [UNESP]; Bottino, Marco Antonio [UNESP]; Özcan, Mutlu (Elsevier, 2019)
The goal of this study was to compare the mechanical response of resin-bonded fixed dental prosthesis (RBFDP)made in zirconia, metal, lithium disilicate and composite resin cemented using resin cements with different elastic modulus. For the finite element analysis, a three-dimensional model of partial right maxilla was used to create a model with edentulous space in the second premolar and the cavity's preparation on the first pre-molar and first molar to receive a RBFDP. The model was imported to the analysis software in which they were divided into mesh composed by nodes (371,101)and tetrahedral elements (213,673). Each material was considered isotropic, elastic and homogeneous. No-separation contacts were considered between restoration/resin cement and resin cement/tooth. For all other structures the contacts were considered ideal. The model fixation occurred at the base of the bone and an axial load of 300 N was applied on the pontic occlusal surface. To simulate polymerization shrinkage effects on the cement, the thermal expansion approach was used. The displacement and maximum principal stress (in MPa)were selected as failure criteria. The prosthesis made in composite resin showed higher displacement, while in zirconia showed higher stress concentration. Tensile stress between restoration/cement, cement and cement/cavity was directly proportional to the restorative material's elastic modulus. The more rigid cement increases the tensile zones in the cement layer but decreases the stress between prosthesis and cement. The molar cavity showed higher stress concentration between restoration/cement than the preparation in the pre-molar tooth. The use of composite resin for the manufacturing of RBFDP increases the displacement of the set during the loading. However, it reduces the amount of stress concentration at the adhesive interface in comparison with the other materials.
Keywords: Dental materials; Finite element analysis; Material properties